The Effect of Environmental Performance on Firm Value with Profitability as a Mediating Variable: An Empirical Study of SRI-KEHATI Indexed Companies Listed on the Indonesia Stock Exchange (2021–2023) - Putri Asrar Fenani; Ahmad Faisol (Journal of Innovative and Creativity, 2025)
This study aims to examine the effect of environmental performance on firm value with profitability as a mediating variable in companies included in the SRI-KEHATI index on the Indonesia Stock Exchange during the 2021–2023 period. Environmental performance is measured using the PROPER score published by the Ministry of Environment and Forestry, profitability is measured by Return on Equity (ROE), and firm value is measured using the Tobin’s Q ratio. This research uses a quantitative method with secondary data obtained from annual reports and PROPER reports of the companies. The research sample was selected using purposive sampling technique, resulting in 6 companies with 18 observations over three years. Data analysis was performed using panel data regression and the Sobel Test for mediation analysis. The results show that environmental performance does not have a significant effect on company profitability, indicating that efforts to improve environmental performance have not been able to provide a direct impact on company profits in the short term. Conversely, profitability is proven to have a positive and significant effect on firm value, confirming that companies with high profitability are more valued by the market. Testing the direct effect of environmental performance on firm value also shows insignificant results, although the direction of the effect is positive. However, the Sobel mediation test results show that profitability significantly mediates the effect of environmental performance on firm value. This means that an increase in environmental performance followed by an increase in profitability will have a positive impact on firm value. This research implies that the integration of environmental and financial strategies is very important in efforts to create sustainable firm value. The limitation of this study lies in the short observation period and the exclusion of other control variables that may affect firm value.